World Crude Oil Markets : Monetary Policy and the Recent Oil Shock - Krichene, Noureddine (IMF Working Papers; Working Paper ;, 2006)
This paper examines the relationship between monetary policy and oil prices within a world oil demand and supply model. Low price and high income elasticities of demand and rigid supply explain high price volatilities and producers' market power. Exchange and interest rates do influence oil market equilibrium. The relationship between oil prices and interest rates is a two-way relationship that depends on the type of oil shock. During a supply shock, rising oil prices caused interest rates to increase; whereas during a demand shock, falling interest rates caused oil prices to rise. Record low interest rates led to high oil price volatility in 2005. Data shows that world economic growth and price stability require stable oil markets and therefore more prudent monetary policies.